Substrate film for vapor deposition and vapor deposition film

By using a substrate film formed by a methacrylic resin composition with a high glass transition temperature and a low water absorption rate, the problem of insufficient heat resistance and dimensional stability of the substrate film in the prior art is solved, and the high temperature is achieved The high-performance vapor-deposited substrate film used.

CN119487109APending Publication Date: 2025-02-18KURARAY CO LTD
View PDF 23 Cites 0 Cited by

Patent Information

Application Number
CN202380054144.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-21
Filing Date
2023-07-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing substrate films are insufficient in heat resistance when used at high temperatures, and the high water absorption rate leads to large changes in size, making it difficult to meet the requirements of the evaporation process.

Method used

A substrate film formed of a methacrylic resin composition (I) containing a methacrylic copolymer (a) has a high glass transition temperature, low saturation water absorption and excellent biaxial pulling Extension.

Benefits of technology

It realizes high heat resistance, flexibility and dimensional stability of the substrate film, is suitable for use in the evaporation process, and improves the adhesion to the evaporation film, giving high performance functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487109A_ABST
    Figure CN119487109A_ABST
Patent Text Reader

Abstract

Provided are: a base film which has high heat resistance, flexibility, and dimensional stability and which is for providing a vapor deposition film on at least one surface thereof; and a vapor deposition film which comprises the base film and the vapor deposition film. A substrate film for vapor deposition, which is formed from a methacrylic resin composition (I) that contains a methacrylic copolymer (a) and has a glass transition temperature of 135 DEG C or higher, and which has a film thickness of 10-80 [mu] m and a biaxial stretching rate of 1.5-8 times. The methacrylic copolymer (a) has 5-73 mass% of methyl methacrylate units, 25-70 mass% of a structural unit (r) represented by formula (1), 1-48 mass% of alpha-methylstyrene units, 1-48 mass% of at least one selected from the group consisting of styrene units and maleic anhydride units, and 0-20 mass% of unsubstituted or N-substituted maleimide units. (In formula (I), R1 and R2 are as described in the description. > # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a vapor deposition substrate film and a vapor deposition film having a vapor deposition film on the vapor deposition substrate film. More specifically, the present invention relates to a film suitable for vapor deposition that has excellent dimensional stability, adhesion to the vapor deposition film, and flexibility, and a vapor deposition film having a conductive layer or a gas barrier layer formed by vapor deposition. Background Art

[0002] A vapor-deposited film is formed on at least one surface of a substrate film to impart various functions to the substrate film. For example, a technique of vapor-depositing a metal such as indium oxide to which tin is added in order to impart design properties, conductivity, etc. to a substrate film is known (e.g., Patent Document 1). In addition, a technique of vapor-depositing an inorganic compound such as silicon oxide in order to impart gas barrier properties, anti-reflection properties, etc. to a substrate film is known (e.g., Patent Document 2).

[0003] The above-mentioned base film is sometimes further required to have excellent light transmittance. Methacrylic resin is a resin with extremely excellent light transmittance. However, methacrylic resin films generally have low adhesion to vapor-deposited films and are difficult to use as vapor-deposited base films.

[0004] As a means to solve the above-mentioned problems, Patent Document 3 proposes a laminated film for direct metal vapor deposition, which is formed by laminating a styrene resin layer (B1) formed by a resin composition (b1) containing a copolymer of a styrene monomer and an olefin cyanide on at least one surface of a thermoplastic resin layer (A) formed by a resin composition (a) containing a methacrylic resin. In addition, Patent Documents 4 and 5 propose acrylic resin films for metal vapor deposition formed by molding a (meth)acrylic resin composition having an acid value of 0.2 to 1.5 mmol / g. However, the heat resistance of the above-mentioned film is insufficient, and the substrate film cannot be used at high temperatures. In addition, there are problems such as heating shrinkage caused by residual strain during molding. Patent Document 6 proposes a substrate film, which is formed by molding a glutarimide acrylic resin having a glutarimide structural unit and a methyl methacrylate structural unit to obtain a film and then biaxially stretching it. In addition, Patent Document 7 proposes a substrate for a transparent conductive film formed by a mixed resin of a polymethylmethacrylimide resin and an acrylic elastomer. However, the above-mentioned film has a high water absorption rate, and there are problems such as degradation of physical properties and large dimensional changes due to water absorption.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 2-6126

[0008] Patent Document 2: Japanese Patent Application Publication No. 2004-276566

[0009] Patent Document 3: Japanese Patent Application Publication No. 2011-143584

[0010] Patent Document 4: Japanese Patent Application Publication No. 2012-57067

[0011] Patent Document 5: Japanese Patent Application Publication No. 2010-236085

[0012] Patent Document 6: Japanese Patent Application Laid-Open No. 6-256537

[0013] Patent Document 7: Japanese Patent Application Publication No. 2020-122125 Summary of the invention

[0014] Problems to be solved by the invention

[0015] In view of the above circumstances, an object of the present invention is to provide a base film having high heat resistance, flexibility and dimensional stability and having a vapor-deposited film on at least one surface thereof, and a vapor-deposited film having the base film and the vapor-deposited film.

[0016] The present inventors have conducted intensive studies to achieve the above-mentioned object, and as a result, have completed the present invention including the following aspects. [1]

[0018] A substrate film for vapor deposition, which is formed from a methacrylic resin composition (I) containing a methacrylic copolymer (a) and having a glass transition temperature of 135° C. or higher, and has a film thickness of 10 to 80 μm and a biaxial stretching ratio of 1.5 to 8 times, wherein the methacrylic copolymer (a) has 5 to 73% by mass of methyl methacrylate units, 25 to 70% by mass of a structural unit (r) represented by the following formula (1), 1 to 48% by mass of an α-methylstyrene unit, 1 to 48% by mass of at least one selected from the group consisting of a styrene unit and a maleic anhydride unit, and 0 to 20% by mass of an unsubstituted or N-substituted maleimide unit.

[0019]

[0020] (In formula (I), R 1 are each independently a hydrogen atom or a methyl group, R 2 It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. [2]

[0022] The vapor deposition substrate film according to [1], which is formed from a methacrylic resin composition having a glass transition temperature of 145° C. or higher. [3]

[0024] The vapor deposition substrate film according to [1], which is formed from a methacrylic resin composition having a saturated water absorption of 3.0% by mass or less. [4]

[0026] A vapor-deposited film comprises the base film described in [1] and a vapor-deposited film provided on at least one surface of the base film. [5]

[0028] The vapor-deposited film according to [4], wherein the vapor-deposited film is a conductive vapor-deposited film. [6]

[0030] The vapor-deposited film according to [4], wherein the vapor-deposited film is a gas barrier vapor-deposited film. [7]

[0032] A method for producing a substrate film according to [1], comprising the steps of forming a methacrylic resin composition (I) containing a methacrylic copolymer (a) and having a glass transition temperature of 135°C or higher to obtain a film, and biaxially stretching the film to 1.5 to 8 times in terms of area ratio, wherein the methacrylic copolymer (a) has 5 to 73% by mass of methyl methacrylate units, 25 to 70% by mass of a structural unit (r) represented by the following formula (1), 1 to 48% by mass of α-methylstyrene units, 1 to 48% by mass of at least one selected from the group consisting of styrene units and maleic anhydride units, and 0 to 20% by mass of unsubstituted or N-substituted maleimide units.

[0033]

[0034] (In formula (I), R 1 are each independently a hydrogen atom or a methyl group, R 2 It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.

[0035] Effects of the Invention

[0036] The substrate film of the present invention has high heat resistance, flexibility and dimensional stability and can be suitably used in a vapor deposition process.

[0037] The vapor-deposited film of the present invention has high adhesion to the vapor-deposited film, and can be endowed with high-performance functions in various applications. The transparent conductive film as one embodiment of the vapor-deposited film of the present invention is useful as a window electrode of a photoelectric conversion element of a solar cell, an electromagnetic shielding film for electromagnetic shielding, a transparent radio wave absorber, an electrode of an input device such as a transparent touch panel, a substrate for a liquid crystal display, an organic EL display or a transparent electrode for a touch panel, etc. In addition, the gas barrier film as another embodiment of the vapor-deposited film of the present invention is useful as a packaging material for food, medicine, etc., an organic EL element, an organic thin film solar cell, an organic transistor, a flexible liquid crystal, etc. DETAILED DESCRIPTION

[0038] In this specification, unless otherwise explicitly stated in the specification or clearly contradicted by the context, the singular forms (a, an, the, etc.) include both the singular and the plural.

[0039] The substrate film of the present invention is a film for evaporation. Evaporation includes physical evaporation and chemical evaporation. The substrate film of the present invention can be appropriately formed by conventionally known physical evaporation methods such as vacuum evaporation, sputtering, and ion plating, or chemical evaporation. Among them, vacuum evaporation is used as a preferred method.

[0040] The methacrylic resin composition (I) used in the vapor deposition substrate film of the present invention contains a methacrylic copolymer (a). In a preferred embodiment, the methacrylic resin composition (I) contains a methacrylic copolymer (a) and a methacrylic resin. The content of the methacrylic copolymer (a) in the methacrylic resin composition (I) is preferably 51% by mass or more, more preferably 65% ​​by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more, and may be composed only of the methacrylic copolymer (a).

[0041] [Methacrylic acid copolymer (a)]

[0042] The methacrylic copolymer (a) of the present invention contains 5 to 73% by mass of methyl methacrylate units, 25 to 70% by mass of structural units (r), 1 to 48% by mass of α-methylstyrene units, 1 to 48% by mass of at least one selected from the group consisting of styrene units and maleic anhydride units, and 0 to 20% by mass of unsubstituted or N-substituted maleimide units. As described above, the methacrylic copolymer (a) also includes a methacrylic copolymer (a) in which the unsubstituted or N-substituted maleimide units are 0% by mass, that is, the methacrylic copolymer (a) does not contain unsubstituted or N-substituted maleimide units. The methacrylic copolymer (a) used in the present invention may also contain other vinyl monomer units that can be copolymerized with methyl methacrylate. In the present invention, the structural unit in the polymer refers to a repeating unit constituting the polymer or a unit formed by derivatizing at least a part of the repeating unit (for example, an unsubstituted or N-substituted glutarimide unit). In addition, in this specification, the methyl methacrylate unit, the structural unit (r), the α-methylstyrene unit, the styrene unit, and other vinyl monomer units are sometimes collectively referred to as the term "structural unit".

[0043] In the methacrylic copolymer (a) of the present invention, the ratio of the methyl methacrylate unit is 5 to 73% by mass, preferably 6 to 70% by mass, more preferably 6 to 60% by mass, and further preferably 6 to 50% by mass relative to the total structural units. From the viewpoint of transparency and thermal decomposition resistance of the obtained methacrylic copolymer, the ratio of the methyl methacrylate unit is preferably within the above range.

[0044] In the methacrylic copolymer (a) of the present invention, the ratio of the α-methylstyrene unit is 1 to 48% by mass, preferably 3 to 40% by mass, more preferably 5 to 35% by mass, and further preferably 7 to 30% by mass relative to the total structural units. The ratio of the α-methylstyrene unit is preferably within the above range from the viewpoints of heat resistance, rigidity, and thermal decomposition resistance of the obtained methacrylic copolymer, productivity (polymerizability), inhibition of hindrance of the glutarimidization reaction caused by intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid described later, heat shrinkage of the substrate film, and dimensional stability of the deposited film.

[0045] In the methacrylic copolymer (a) of the present invention, the ratio of styrene units or maleic anhydride units is 1 to 48% by mass, preferably 3 to 40% by mass, more preferably 5 to 35% by mass, and further preferably 7 to 30% by mass, relative to all structural units. From the viewpoints of the heat decomposition resistance, fluidity, and heat resistance of the obtained methacrylic copolymer, and the viewpoints of inhibiting the glutarimidization reaction caused by the intramolecular cyclization of two adjacent structural units derived from (meth) acrylic acid described later, and the viewpoints of the stretchability of the unstretched film, etc., it is preferred that the ratio of styrene units is within the above range. From the viewpoints of the heat decomposition resistance, fluidity of the obtained methacrylic copolymer, and the viewpoints of inhibiting the glutarimidization reaction caused by the intramolecular cyclization of two adjacent structural units derived from (meth) acrylic acid described later, and the viewpoints of the stretchability of the unstretched film, etc., it is preferred that the ratio of maleic anhydride units is within the above range. In the present invention, it is preferred to include styrene units with better productivity.

[0046] In the methacrylic copolymer (a) of the present invention, the total ratio of α-methylstyrene units and styrene units is preferably 2 to 40% by mass, more preferably 5 to 35% by mass, and further preferably 10 to 30% by mass relative to all structural units. When the total ratio of α-methylstyrene units and styrene units is within the above range, it is not easy to hinder the glutarimidization reaction caused by the intramolecular cyclization of two adjacent structural units derived from (meth) acrylic acid described later. In addition, relative to the total ratio of α-methylstyrene units and styrene units, the ratio of α-methylstyrene units is preferably 30 to 95% by mass, more preferably 35 to 90% by mass, and further preferably 40 to 85% by mass. When the ratio of α-methylstyrene units is within the above range, the methacrylic copolymer used in the present invention has an excellent balance between heat resistance and low water absorption, so the dimensional stability of the obtained film is good.

[0047] The structural unit (r) is a structural unit having a ring structure selected from the group consisting of N-substituted or unsubstituted glutarimide units in the main chain.

[0048] The N-substituted or unsubstituted glutarimide unit is a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure. Examples of the unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure include a structural unit represented by formula (I).

[0049]

[0050] In formula (I), R 1 Each independently represents a hydrogen atom or a methyl group, preferably 2 R 1 All are methyl. 2It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms containing an aromatic ring, preferably a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, more preferably a methyl group, an n-butyl group, or a cyclohexyl group, and most preferably a methyl group.

[0051] In addition, the structural unit (r) can be formed, for example, by adding an imidizing agent to a precursor polymer in an extruder, kneading, and reacting the imide cyclization reaction. In a preferred embodiment, the structural unit represented by formula (I) can be formed, for example, by reacting the corresponding acid anhydride (IIa) with R 2 It can be generated by the reaction of an imidizing agent represented by NH2, or by an intramolecular cyclization reaction of a copolymer having a partial structure of formula (III). In order to convert the structural unit represented by formula (III) into the structural unit represented by formula (I) by the intramolecular cyclization reaction, it is preferably heated.

[0052] Solution (i)

[0053]

[0054] (Where R 1 , R 2 As defined above.)

[0055] The N-substituted or unsubstituted glutarimide unit can be obtained by the method described in WO2005 / 10838A1, Japanese Patent Application Laid-Open No. 2010-254742, Japanese Patent Application Laid-Open No. 2008-273140, Japanese Patent Application Laid-Open No. 2008-274187, etc., specifically, by reacting an imidizing agent such as ammonia, methylamine, ethylamine, diethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, etc., an amine containing an aliphatic hydrocarbon group such as aniline, toluidine, trichloroaniline, N-methylbenzylamine, etc., an amine containing an aromatic hydrocarbon group such as cyclohexylamine, N-methylcyclohexylamine, etc., an amine containing an alicyclic hydrocarbon group such as urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea, with two adjacent structural units derived from methyl methacrylate or glutaric anhydride units. Among them, primary amine is essential, and secondary amine can also be used in combination. As the primary amine, methylamine is preferred. During the imidization reaction, a part of the methyl methacrylate unit is sometimes hydrolyzed to become a carboxyl group, and the carboxyl group is preferably restored to the original methyl methacrylate unit by an esterification reaction treated with an esterifying agent. As the esterifying agent, there is no particular limitation as long as it is within the range that can exert the effect of the present application, and dimethyl carbonate and the like can be preferably used. In addition, in addition to the esterifying agent, tertiary amines such as trimethylamine, triethylamine, and tributylamine can also be used in combination as a catalyst.

[0056] In the methacrylic acid copolymer (a) of the present invention, the ratio of the structural unit (r) is 25 to 70% by mass, preferably 30 to 68% by mass, more preferably 35 to 65% by mass, and further preferably 40 to 60% by mass relative to the total structural units. From the viewpoints of heat resistance, thermal decomposition resistance, low water absorption, and molding processability of the obtained methacrylic acid copolymer, as well as the heat shrinkage rate of the substrate film, the adhesion to the deposited layer, and the dimensional stability of the deposited film, the ratio of the structural unit (r) is preferably within the above range.

[0057] The methacrylic copolymer (a) of the present invention may further contain an N-substituted or unsubstituted maleimide unit in addition to the structural unit (r) etc. The N-substituted or unsubstituted maleimide unit is a unit having an N-substituted or unsubstituted 2,5-pyrrolidinedione structure.

[0058] As the unit having an N-substituted or unsubstituted 2,5-pyrrolidinedione structure, a structural unit represented by formula (VI) can be mentioned.

[0059]

[0060] (In formula (VI), R 10 It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.

[0061] The structural unit represented by formula (VI) can be obtained by polymerizing a monomer mixture containing the monomer represented by formula (VI), polymerizing a monomer mixture containing maleic anhydride, and reacting the maleic anhydride monomer in the reaction product obtained by polymerizing the monomer mixture containing maleic anhydride with the monomer represented by R 3 The methacrylic acid-based copolymer is contained in the methacrylic acid-based copolymer by reaction with an imidizing agent represented by NH2.

[0062] The N-substituted or unsubstituted maleimide unit can be obtained by the method described in Japanese Patent Publication No. 61-026924, Japanese Patent Publication No. 7-042332, Japanese Patent Publication No. 9-100322, Japanese Patent Publication No. 2001-329021, etc., specifically, by reacting an imidizing agent such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, etc., an amine containing an aliphatic hydrocarbon group, aniline, toluidine, trichloroaniline, etc., an amine containing an alicyclic hydrocarbon group, such as cyclohexylamine, urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea, with a maleic anhydride unit. Among them, methylamine is preferred.

[0063] The methacrylic copolymer (a) of the present invention may contain a lactone ring unit as a structural unit derived from other vinyl monomer units in addition to the structural unit (r) and the like. The lactone ring unit is a structural unit containing a >CH-OC(=O)- group in the ring structure. The number of ring constituent elements of the structural unit containing a >CH-OC(=O)- group in the ring structure is preferably 4 to 8, more preferably 5 to 6, and most preferably 6. As the structural unit containing a >CH-OC(=O)- group in the ring structure, lactone diyl structural units such as β-propiolactone diyl structural unit, γ-butyrolactone diyl structural unit, and δ-valerolactone diyl structural unit can be cited. The structural unit containing a >CH-OC(=O)- group in the ring structure can be obtained, for example, by intramolecular cyclization of a polymer having a hydroxyl group and an ester group using the hydroxyl group and the ester group. It should be noted that ">C" in the formula means that there are two bonds on the carbon atom C.

[0064] For example, as the δ-valerolactone diyl structural unit, there can be mentioned a structural unit represented by the formula (IV).

[0065]

[0066] In formula (IV), R 6 , R 7 and R 8 Each independently represents a hydrogen atom or an organic group having 1 to 20 carbon atoms, preferably a hydrogen atom or an organic group having 1 to 10 carbon atoms, and more preferably a hydrogen atom or an organic group having 1 to 5 carbon atoms. Here, the organic group is not particularly limited as long as it has 1 to 20 carbon atoms, and examples thereof include a linear or branched alkyl group, a linear or branched aryl group, an -OCOCH3 group, a -CN group, etc. The organic group may contain heteroatoms such as an oxygen atom. R 6 and R 7 Preferably, methyl, R 8 Preferred is a hydrogen atom.

[0067] The lactone ring unit can be included in the methacrylic acid-based copolymer by the methods described in JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, JP-A-2005-146084, etc., for example, by intramolecular cyclization of a structural unit derived from 2-(hydroxyalkyl)acrylate and a structural unit derived from methyl (meth)acrylate.

[0068] The methacrylic acid copolymer (I) of the present invention may further contain a glutaric anhydride unit as a structural unit derived from other vinyl monomer units in addition to the structural unit (r). The glutaric anhydride unit is a unit having a 2,6-dioxodihydropyrandiyl structure. As the unit having a 2,6-dioxodihydropyrandiyl structure, a structural unit represented by formula (V) can be cited.

[0069]

[0070] In formula (V), R 9 Each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and is preferably a methyl group.

[0071] The unit having a 2,6-dioxodhidropyrandiyl structure can be included in the methacrylic acid-based copolymer by the methods described in JP-A-2007-197703 and JP-A-2010-96919, for example, by intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid, intramolecular cyclization of a structural unit derived from (meth)acrylic acid and a structural unit derived from methyl (meth)acrylate, and the like.

[0072] The methacrylic copolymer (a) of the present invention may contain other vinyl monomer units copolymerizable with the methyl methacrylate unit. The other vinyl monomer units may be selected from materials appropriately according to the properties required of the methacrylic copolymer (a). When properties such as thermal stability, fluidity, chemical resistance, optical properties, and compatibility with other resins are particularly required, at least one selected from the group consisting of acrylic ester monomer units, aromatic vinyl monomer units other than styrene and α-methylstyrene, and vinyl cyanide monomer units is suitable.

[0073] Among the monomers constituting the above-mentioned monomer units, at least one selected from the group consisting of methyl acrylate, ethyl acrylate, and acrylonitrile is preferred from the viewpoint of availability.

[0074] Examples of other vinyl monomer units copolymerizable with methyl methacrylate include methacrylic acid amide units represented by the following formula (A) and 2-(hydroxyalkyl)acrylate units represented by the following formula (B).

[0075]

[0076] (Where R 3 R is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring, preferably a hydrogen atom, a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, and more preferably a methyl group, an n-butyl group, or a cyclohexyl group.4 and R 5 Each independently represents a hydrogen atom or an organic group having 1 to 20 carbon atoms, preferably a hydrogen atom or an organic group having 1 to 10 carbon atoms, and more preferably a hydrogen atom or an organic group having 1 to 5 carbon atoms. Here, the organic group is not particularly limited as long as it has 1 to 20 carbon atoms, and examples thereof include a linear or branched alkyl group, a linear or branched aryl group, an -OCOCH3 group, a -CN group, and the like. The organic group may contain heteroatoms such as an oxygen atom. R 4 Preferably, methyl, R 5 Preferably it is a hydrogen atom.)

[0077] In the methacrylic copolymer (a) of the present invention, the ratio of other vinyl monomer units copolymerizable with methyl methacrylate units is preferably 0 to 20% by mass, more preferably 0 to 15% by mass, and further preferably 0 to 10% by mass relative to all structural units. A methacrylic copolymer in which the ratio of other vinyl monomer units copolymerizable with methyl methacrylate units is greater than 20% by mass has reduced heat resistance and rigidity. It should be noted that the ratio of each monomer unit can be adjusted by 1 H-NMR, 13 C-NMR, infrared spectroscopy, etc.

[0078] The weight average molecular weight (Mw) of the methacrylic copolymer (a) of the present invention is preferably 40,000 to 250,000, more preferably 50,000 to 200,000, and further preferably 60,000 to 180,000. When Mw is 40,000 or more, the methacrylic resin composition (I) of the present invention has excellent impact resistance. When Mw is 250,000 or less, the fluidity of the methacrylic resin composition (I) of the present invention is improved, and the molding processability is improved.

[0079] The weight average molecular weight (Mw) is a value calculated by converting a chromatogram measured by gel permeation chromatography into a molecular weight of standard polystyrene.

[0080] The glass transition temperature of the methacrylic copolymer (a) of the present invention is preferably 135°C or higher, more preferably 140°C, and further preferably 145°C. The upper limit is not particularly limited, but is preferably 170°C.

[0081] In this specification, "glass transition temperature (Tg)" is measured according to JIS K7121. Specifically, the temperature is raised to 250°C once, then cooled to room temperature, and then raised from room temperature to 250°C at a rate of 10°C / min, and a DSC curve is measured under such conditions. The midpoint obtained from the DSC curve measured at the second heating is obtained as the "glass transition temperature (Tg)".

[0082] The melt flow rate (hereinafter referred to as "MFR") of the methacrylic copolymer (a) of the present invention is preferably in the range of 1.0 to 30 g / 10 minutes. The lower limit of the MFR is more preferably 1.5 g / 10 minutes or more, and further preferably 2.0 g / 10 minutes. In addition, the upper limit of the MFR is more preferably 25 g / 10 minutes or less, and further preferably 20 g / 10 minutes or less. When the MFR is in the range of 1.0 to 30 g / 10 minutes, the stability of heated melt molding is good. It should be noted that the MFR of the methacrylic copolymer (a) in this specification refers to the value measured at a temperature of 230°C and a load of 3.8 kg using a melt indexer according to JIS K7210.

[0083] The saturated water absorption rate of the methacrylic acid copolymer (a) of the present invention can be measured under the following conditions. The methacrylic acid copolymer is formed into a sheet with a thickness of 1.0 mm by press molding. A 50 mm × 50 mm test piece is cut out from the center of the obtained pressed sheet and dried in a 90°C dryer for more than 16 hours. The dried test piece is cooled to room temperature in a dryer, and then the weight is measured to 0.1 mg, and the weight is set as the initial weight W0. The test piece is immersed in distilled water at 23°C. After immersion for 24 hours, the test piece is taken out of the water, and all the moisture on the surface is wiped off with a clean and dry cloth or filter paper. Within 1 minute after being taken out of the water, weigh the test piece again to 0.1 mg. The test piece is immersed again, and the weight is measured again by the same method as above after 24 hours. The weight of the test piece when the weight change rate reaches within 0.02% of W0 is set as the saturated weight W S The saturated water absorption rate can be calculated by formula (1).

[0084] Saturated water absorption rate = [(W S -W0) / W0]×100 (1)

[0085] The saturated water absorption is preferably 3.0% by mass or less, more preferably 2.7% by mass or less, and further preferably 2.5% by mass or less.

[0086] [Methacrylic resin]

[0087] The methacrylic resin composition (I) of the present invention may contain a methacrylic resin. The content of the methacrylic resin is preferably 1 to 49% by mass, more preferably 5 to 40% by mass, and further preferably 10 to 30% by mass. The methacrylic resin composition (I) of the present invention improves fluidity by containing a methacrylic resin.

[0088] The methacrylic resin is a resin containing a structural unit derived from methacrylate. Examples of the methacrylate include methyl methacrylate (hereinafter referred to as "MMA"), ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, dodecyl methacrylate and other alkyl methacrylates; 1-methylcyclopentyl methacrylate, cyclohexyl methacrylate, cycloheptyl methacrylate, cyclooctyl methacrylate, tricyclo[5.2.1.0]methacrylate. 2,6 ] cycloalkyl methacrylates such as decyl-8-yl ester; aryl methacrylates such as phenyl methacrylate; aryl methacrylates such as benzyl methacrylate; etc., from the viewpoint of availability, MMA, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate and tert-butyl methacrylate are preferred, and MMA is most preferred. Methacrylates can be used alone or in combination of two or more. The content of the structural unit derived from methacrylate in the methacrylic resin is preferably 90% by mass or more, more preferably 95% by mass or more, and further preferably 98% by mass or more, and may be only structural units derived from methacrylate.

[0089] The lower limit of the syndiotacticity (rr) of the methacrylic resin in terms of triad is preferably 56% or more, more preferably 57% or more, and even more preferably 58% or more. When the lower limit of the content of this structure is 56% or more, the methacrylic resin composition (I) of the present invention has excellent heat resistance.

[0090] Here, the syndiotacticity (rr) calculated on a triad basis (hereinafter sometimes referred to as "syndiotacticity (rr)") is the ratio of two chains (diads) possessed by a chain of three consecutive structural units (triad) being both racemic (denoted as rr). It should be noted that, among the chains (diads) of structural units in a polymer molecule, chains having the same stereo configuration are called meso, and chains having opposite stereo configurations are called racemo, and are denoted as m and r, respectively.

[0091] The syndiotacticity (rr) (%) of the methacrylic resin can be measured in deuterated chloroform at 30°C. 1H-NMR spectrum, from which the area (Y) of the region of 0.6 to 0.95 ppm and the area (Z) of the region of 0.6 to 1.35 ppm when tetramethylsilane (TMS) was set to 0 ppm were measured, and calculated by the formula: (Y / Z)×100.

[0092] The weight average molecular weight (hereinafter referred to as "Mw") of the methacrylic resin is preferably 40000 to 500000, more preferably 60000 to 300000, and even more preferably 80000 to 200000. When the Mw is 40000 or more, the methacrylic resin composition (I) of the present invention has excellent mechanical strength, and when the Mw is 500000 or less, the fluidity becomes good.

[0093] The glass transition temperature of the methacrylic resin is preferably 100° C. or higher, more preferably 105° C. or higher, and further preferably 110° C. or higher. When the glass transition temperature is 100° C. or higher, the methacrylic resin composition (I) of the present invention has excellent heat resistance.

[0094] The saturated water absorption of the methacrylic resin in water at 23° C. is preferably 2.5% by mass or less, more preferably 2.3% by mass or less, and even more preferably 2.1% by mass or less. When the saturated water absorption is 2.5% by mass or less, the methacrylic resin composition (I) of the present invention has excellent moisture resistance and can suppress curling due to moisture absorption.

[0095] The MFR of the methacrylic resin is preferably in the range of 1 to 20 g / 10 minutes. The lower limit of the MFR is more preferably 1.2 g / 10 minutes or more, and further preferably 1.5 g / 10 minutes or more. In addition, the upper limit of the MFR is more preferably 15 g / 10 minutes or less, and further preferably 10 g / 10 minutes or less. When the MFR is in the range of 1 to 10 g / 20 minutes, the stability of the heated melt molding is good.

[0096] [Methacrylic resin composition (I)]

[0097] The glass transition temperature of the methacrylic resin composition (I) of the present invention is 135° C. or higher, preferably 140° C., more preferably 145° C., and the upper limit is not particularly limited, but is preferably 170° C. When the glass transition temperature is 135° C. or higher, the heat shrinkage of the substrate film of the present invention can be reduced.

[0098] The melt flow rate (hereinafter referred to as "MFR") of the methacrylic resin composition (I) of the present invention is preferably in the range of 1.0 to 30 g / 10 minutes. The lower limit of the MFR is more preferably 1.5 g / 10 minutes or more, and further preferably 2.0 g / 10 minutes. In addition, the upper limit of the MFR is more preferably 25 g / 10 minutes or less, and further preferably 20 g / 10 minutes or less. When the MFR is in the range of 1.0 to 30 g / 10 minutes, the stability of heat-melt molding is good.

[0099] The saturated water absorption of the methacrylic resin composition (I) of the present invention is preferably 3.0% by mass or less, more preferably 2.5% by mass or less, and further preferably 2.0% by mass or less. When the saturated water absorption is 3.0% by mass or less, the substrate film of the present invention has excellent dimensional stability.

[0100] The total light transmittance of the methacrylic resin composition (I) of the present invention is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. When the total light transmittance is 80% or more, the transparency of the substrate film of the present invention is good. It should be noted that the total light transmittance of the methacrylic resin composition is a value measured using a haze meter and a pressed sheet with a thickness of 3 mm according to JIS K7361-1.

[0101] The methacrylic resin composition (I) of the present invention may contain a filler as required within the range not impairing the effects of the present invention. Examples of fillers include calcium carbonate, talc, carbon black, titanium oxide, silica, clay, barium sulfate, magnesium carbonate, etc. The amount of filler that may be contained in the resin composition of the present invention is preferably 3% by mass or less, more preferably 1.5% by mass or less.

[0102] The methacrylic resin composition (I) of the present invention may contain other polymers within the range not impairing the effects of the present invention. Examples of other polymers include polyolefin resins such as polyethylene, polypropylene, polybutene-1, poly-4-methylpentene-1, and polynorbornene; ethylene ionomers; styrene resins such as polystyrene, styrene-maleic anhydride copolymer, high-impact polystyrene, AS resin, ABS resin, AES resin, AAS resin, ACS resin, and MBS resin; methyl methacrylate-styrene copolymers; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; nylon 6, nylon 66, and polyamide elastomers; Polyamide; polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyacetal, polyvinylidene fluoride, polyurethane, phenoxy resin, modified polyphenylene ether, polyphenylene sulfide, silicone modified resin; silicone rubber; acrylic multilayer copolymer elastomer; acrylic thermoplastic elastomers such as diblock copolymers and triblock copolymers of methyl methacrylate polymer block-n-butyl acrylate polymer block; styrene thermoplastic elastomers such as SEPS, SEBS, and SIS; olefin rubbers such as IR, EPR, and EPDM, etc. The amount of other polymers that can be contained in the methacrylic resin composition (I) of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, and most preferably 0% by mass.

[0103] The methacrylic resin composition (I) of the present invention may contain additives such as antioxidants, heat degradation inhibitors, ultraviolet absorbers, light stabilizers, lubricants, mold release agents, polymer processing aids, antistatic agents, flame retardants, dyes / pigments, light diffusers, organic pigments, matting agents, and phosphors within a range that does not impair the effects of the present invention.

[0104] These additives can be used alone or in combination of two or more. In addition, these additives can be added to the polymerization reaction solution when manufacturing the methacrylic copolymer (a), can be added to the manufactured methacrylic copolymer (a), and can also be added when preparing the methacrylic resin composition (I) of the present invention. From the viewpoint of suppressing the poor appearance of the molded body, the total amount of the additives contained in the methacrylic resin composition (I) of the present invention is preferably 7% by mass or less, more preferably 5% by mass or less, and further preferably 4% by mass or less relative to the methacrylic resin composition (I).

[0105] The preparation method of the methacrylic resin composition (I) of the present invention is not particularly limited. For example, a method of polymerizing a monomer mixture containing methyl methacrylate and the like in the presence of a methacrylic resin to generate a methacrylic copolymer (a) and a method of melt-kneading the methacrylic copolymer (a) and the methacrylic resin can be cited. During melt-kneading, other polymers and additives can be mixed as needed, or the methacrylic copolymer (a) can be mixed with other polymers and additives and then mixed with the methacrylic resin, or the methacrylic resin can be mixed with other polymers and additives and then mixed with the methacrylic copolymer (a), or other methods can be used. Kneading can be carried out using a known mixing device or kneading device such as a kneader, an extruder, a mixing roll, a Banbury mixer, etc. Among them, a twin-screw extruder is preferred.

[0106] [Base film for vapor deposition]

[0107] The vapor deposition substrate film of the present invention can be produced by shaping the above-mentioned methacrylic resin composition (I). In addition, from the viewpoint of improving mechanical strength, the substrate film of the present invention can be produced by shaping the above-mentioned methacrylic resin composition (I) to obtain a raw film and stretching the raw film.

[0108] The molding method of the methacrylic resin composition is not particularly limited. Examples of the molding method include solution casting, melt casting, extrusion molding, inflation molding, blow molding, and calendering. Among them, extrusion molding is preferred from the viewpoint of productivity. The set temperature of the methacrylic resin composition discharged from the extruder is preferably 180 to 280° C., more preferably 200 to 260° C.

[0109] The extrusion molding method can adopt the known method used in the film molding of the usual thermoplastic resin. For example, from the viewpoints of good surface smoothness, good gloss, low haze, etc., the molding can be performed using a device having a flat T-die and two or more metal polished rollers or belts with mirror-finished surfaces. The linear pressure between a pair of mirror-finished rollers or mirror-finished belts is preferably 10 N / mm or more, more preferably 30 N / mm.

[0110] The surface temperature of the mirror-finished roller or the mirror-finished belt is preferably 130° C. or lower. In addition, the surface temperature of at least one of the pair of mirror-finished rollers or the mirror-finished belt is preferably 60° C. or higher. When the surface temperature is set to this level, the methacrylic resin composition discharged from the extruder can be cooled at a faster rate than natural cooling, and a film having excellent surface smoothness and low haze can be easily obtained.

[0111] The methacrylic resin composition is preferably melt-filtered using a filter before molding. By using the methacrylic resin composition that has been melt-filtered for molding, it is easy to obtain a film with few defects from foreign matter, gel, etc. There is no particular restriction on the filter used in the melt filtration. From the viewpoints of the use temperature, viscosity, required filtration accuracy, etc., the filter can be appropriately selected from known filters. Specific examples of the filter include: non-woven fabrics composed of glass fibers, etc.; cellulose films impregnated with phenolic resins; metal fiber non-woven fabric sintered films; metal powder sintered films; metal mesh; or combinations thereof. Among them, from the viewpoints of heat resistance, durability and pressure resistance, it is preferred to use multiple metal fiber non-woven fabric sintered films stacked together. The filtration accuracy of the above-mentioned filter is not particularly limited, and is preferably 30 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less.

[0112] The stretching treatment can adopt the method used in the field of resin film. The stretching treatment is usually carried out in sequence through the processes of heating, stretching, heat fixing and cooling. Through this stretching treatment, the mechanical strength is improved, and a substrate film that is not easy to break can be obtained. As a stretching method, for example, a uniaxial stretching method, a simultaneous biaxial stretching method, a sequential biaxial stretching method, a tubular stretching method, etc. can be cited. From the viewpoint of being able to stretch uniformly and obtain a high-strength film, the temperature during stretching is preferably 100 to 200°C, and more preferably 120 to 160°C. The stretching speed during stretching is preferably 100 to 5000% / minute based on the length. The stretching ratio in biaxial stretching is preferably 1.5 to 8 times in terms of area ratio. After stretching, by implementing heat fixing or relaxing the stretched film, a substrate film with less heat shrinkage can be obtained. In the present invention, the stretching ratio in biaxial stretching can be measured based on the length and width of the film before and after stretching.

[0113] The thickness of the vapor deposition substrate film of the present invention is 10 to 50 μm, preferably 15 to 40 μm.

[0114] The total light transmittance of the vapor deposition substrate film of the present invention is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. With a total light transmittance of 80% or more, the appearance quality of the vapor deposition substrate film obtained in the present invention is excellent. The total light transmittance can be measured by a method based on JIS K7105.

[0115] In the substrate film for vapor deposition of the present invention, the surface wetting tension of the layer formed by the methacrylic resin composition (I) is preferably 38 mN / m or more, more preferably 39 mN / m or more, and further preferably 40 mN / m or more. When the surface wetting tension is at least 38 mN / m or more, the bonding strength between the substrate film for vapor deposition of the present invention and the vapor-deposited film is improved. In order to adjust the surface wetting tension, for example, corona discharge treatment, ozone blowing, ultraviolet irradiation, flame treatment, chemical reagent treatment, and other previously known surface treatments can be implemented. The wetting tension can be measured by a method based on JIS K6768.

[0116] [Evaporated film]

[0117] The vapor-deposited film of the present invention comprises a substrate film of the present invention and a vapor-deposited film disposed on at least one surface of the substrate film. The vapor-deposited film is disposed to impart various functions to the film. Examples of such functions include decoration, scratch resistance, antistatic, antifouling, friction reduction, anti-glare, light reflection prevention, high light reflection, adhesion, impact resistance, anti-adhesion, conductivity, and gas barrier. As described above, it can also be understood that the vapor-deposited film of the present invention is laminated with a vapor-deposited film on at least one surface of the substrate film of the present invention, and therefore the vapor-deposited film of the present invention can also be referred to as the laminated film of the present invention.

[0118] The materials used in the vapor-deposited film are not particularly limited, and examples thereof include: elemental metals, elemental metalloids, inorganic compounds, organic compounds, and the like. As inorganic compounds, oxides and oxynitrides of Si, Al, In, Sn, Zn, Ti, Cu, Ce, Ta, and the like are preferred. As organic compounds, organic polymer compounds are preferred. In addition, polysiloxanes, polyparaxylene, polyurethanes (diisocyanates / diols), polyureas (diisocyanates / diamines), polythioureas (dithioisocyanates / diamines), polythioether carbamates (bisethylene carbamates / dithiols), polyimines (diepoxy / primary amines), polypeptide amides (bis-azlactones / diamines), polyamides (diolefins / diamides), and other addition polymers, acrylate polymers, and the like can be used.

[0119] One or more vapor-deposited films made of at least one selected from these materials may be provided on one or both surfaces of the base film.

[0120] Vapor-deposited films made of silicon oxide, silicon oxynitride, aluminum oxide, etc. have excellent light transmittance and are suitable for optical applications.

[0121] Polysiloxane is formed by introducing vapor obtained by heating and evaporating hexamethyldisiloxane into a parallel plate plasma device using RF electrodes, and depositing on a substrate film while undergoing a polymerization reaction in the plasma. The vapor-deposited film composed of polysiloxane can be easily hydrophilized by oxygen plasma, etc., has good adhesion to inorganic vapor-deposited films, and has excellent bending resistance.

[0122] For polyparaxylene, for example, polyparaxylene is heated and evaporated in a high vacuum, and the vapor is heated to 650°C to 700°C to thermally decompose polyparaxylene to generate free radicals. When the free radicals are introduced into a chamber provided with a substrate film, the free radicals are adsorbed on the substrate film and free radical polymerization is performed to form a polyparaxylene film. The evaporated film formed of polyparaxylene has excellent mechanical strength, thermal strength, chemical strength, etc.

[0123] The addition polymer is formed by, for example, depositing the above-mentioned monomers on a substrate film in a vacuum while performing addition polymerization. Among the addition polymers, polyurea is preferred from the viewpoints of transparency, material cost, and the like.

[0124] In order to impart the function of preventing light reflection, for example, a vapor-deposited film having a refractive index lower than that of the base film is disposed on the surface of the base film, or a vapor-deposited film having a high refractive index and a vapor-deposited film having a low refractive index are disposed in sequence on the surface of the base film.

[0125] In order to give the conductive function, for example, the conductive layer comprising the metal oxide is arranged on the substrate film. As required, there can be a refractive index matching layer, a hard coat and / or an anti-adhesion hard coat. About the refractive index matching layer, the hard coat, the anti-adhesion layer, the formation known in the industry can be adopted, so detailed description is omitted.

[0126] Examples of the material constituting the conductive layer include indium oxide, tin oxide, zinc oxide, indium-tin composite oxide, tin-antimony composite oxide, zinc-aluminum composite oxide, indium-zinc composite oxide, etc. Among them, indium-tin composite oxide (ITO) is preferred.

[0127] In order to impart the gas barrier function, for example, a dense vapor-deposited film (gas barrier vapor-deposited film) is provided on the surface of the base film to such an extent that gas molecules to be blocked, such as water molecules and oxygen molecules, cannot pass through.

[0128] Examples of materials constituting the gas barrier deposited film include: elemental metals such as aluminum, nickel, chromium, iron, cobalt, zinc, gold, silver, and copper, and metal alloys consisting of combinations thereof; elemental metalloids such as silicon, germanium, and carbon (diamond-like carbon, graphite, etc.); oxides such as silicon oxide, aluminum oxide, magnesium oxide, indium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, zinc oxide, cerium oxide, hafnium oxide, and barium oxide; nitrides such as silicon nitride, aluminum nitride, boron nitride, and magnesium nitride; carbides such as silicon carbide; oxycarbides; nitrogen carbides; oxynitrides; oxynitrogen carbides; sulfides, etc.

[0129] Among these materials, at least one inorganic compound selected from the group consisting of oxides, nitrides, carbides, oxycarbides, nitrogen carbides, oxynitrides and oxynitride carbides is preferred. The inorganic compound is preferably a silicon compound (Si), an aluminum compound (Al), an indium compound (In), a tin compound (Sn), a zinc compound (Zn), a titanium compound (Ti), a copper compound (Cu) or a tantalum compound (Ta), more preferably a silicon compound (Si), an aluminum compound (Al), an indium compound (In), a tin compound (Sn), a zinc compound (Zn) or a titanium compound (Ti), most preferably a silicon compound or an aluminum compound. These materials can be used alone or in combination of two or more. For example, the above-mentioned inorganic compound can be used in combination with an elemental metal or an elemental metalloid.

[0130] The obtained vapor-deposited film can be analyzed using, for example, a surface analysis device such as a photoelectron spectrophotometer, an X-ray photoelectron spectrometer (XPS), or a secondary ion mass spectrometer (SIMS). These devices can analyze the vapor-deposited film in the thickness direction by ion etching.

[0131] The vapor-deposited film in the vapor-deposited film of the present invention may be a vapor-deposited film having two or more layers of films composed of different types or the same type of materials stacked on top of each other. As an example, a transparent conductive film is provided on a gas-barrier vapor-deposited film in order to improve the stability of the resistance value and the heat-resistant stability of the transparent conductive film. The thickness of such a gas-barrier vapor-deposited film is not particularly limited, and for example, it is preferably 0.001 to 1 μm, more preferably 0.002 to 0.1 μm, and further preferably 0.003 to 0.05 μm. As a specific example of the gas-barrier vapor-deposited film, a film composed of a metal oxide, a metal nitride or a mixture thereof is preferred.

[0132] As another example, in order to protect the gas barrier vapor-deposited film or to improve the gas barrier properties, one or more vapor-deposited films may be further provided on the gas barrier vapor-deposited film. The thickness of such a protective vapor-deposited film is not particularly limited, and is preferably 0.01 μm to 10 μm, more preferably 0.03 μm to 5 μm, and further preferably 0.05 μm to 1 μm. Specific examples of protective vapor-deposited films include vapor-deposited films composed of metal oxides or metal oxynitrides, and vapor-deposited films composed of organic polymer materials.

[0133] The thickness of the vapor-deposited film can be set according to the function to be imparted, preferably 30 to 2000 nm, more preferably 50 to 1500 nm, further preferably 100 to 1000 nm, and most preferably 200 to 800 nm. From the viewpoint of suppressing the occurrence of spots and defects on the vapor-deposited film when it is too thin, suppressing costs, suppressing the reduction of light transmittance, and suppressing coloration, the thickness of the vapor-deposited film is preferably set to the above range.

[0134] The deposited film can be formed by a known evaporation method. As the evaporation method, physical evaporation methods (PVD methods) such as vacuum evaporation, sputtering, and ion plating can be listed; chemical evaporation methods (CVD methods) such as reduced pressure chemical evaporation, catalyst chemical evaporation, and plasma chemical evaporation. From the viewpoint of high-speed film formation and good adhesion to the substrate, the chemical evaporation method is preferred, and the plasma chemical evaporation method is more preferred. As the plasma source method used in the plasma chemical evaporation method, it can be listed: capacitively coupled plasma (parallel plate type) using parallel plate electrodes, inductively coupled plasma (coil method), microwave-excited plasma using surface waves, etc. It is preferred to use an inductively coupled method that can efficiently plasmatize the raw gas molecules.

[0135] The deposition can be performed by combining plasma chemical deposition with other chemical deposition methods (for example, catalytic chemical deposition, etc.) The combination of plasma chemical deposition and catalytic chemical deposition can achieve a process with minimal plasma damage and a high film formation rate.

[0136] Before vapor deposition, the surface of the substrate film may be subjected to surface treatment within a range that does not impair the purpose of the present invention. Examples of surface treatment include: discharge treatment methods such as low-temperature plasma treatment and corona discharge treatment; chemical reagent treatment methods such as acid treatment, alkali treatment, and organic solvent treatment; treatment methods by applying a primer coating (forming an anchor layer); etc. Carbonyl groups, carboxyl groups, hydroxyl groups, etc. can be increased by the discharge treatment method, and polar groups such as amino groups, hydroxyl groups, and carbonyl groups can be increased by the chemical reagent treatment method.

[0137] The anchoring layer is not particularly limited. For example, as long as the anchoring layer has good adhesion to the layer formed by the methacrylic resin composition (I) and good acceptance of the material constituting the vapor-deposited film, it can be an acrylic resin, a nitrocellulose resin, a polyurethane resin (including a resin obtained by curing it with a polyol resin as a main agent and an isocyanate resin as a curing agent), an acrylic urethane resin (including a resin obtained by curing it with an acrylic polyol resin as a main agent and an isocyanate resin as a curing agent), a polyester resin, a styrene-maleic acid resin, a chlorinated PP resin, etc. Among them, from the viewpoint of better adhesion, the anchoring layer preferably contains an acrylic resin.

[0138] The acrylic resin is not particularly limited and may be included in the above-mentioned methacrylic resin. The thickness of the anchor layer is preferably 0.1 to 3 μm. When the thickness of the anchor layer is within the above-mentioned range, the layer formed of the methacrylic resin composition (I) of the vapor-deposited film has excellent adhesion to the vapor-deposited film.

[0139] The anchoring layer can be given design by adding a colorant or a metallic pigment. For example, by adding a yellow pigment as a colorant, the film can have a golden appearance. The type and content of the colorant can be appropriately adjusted according to the desired metallic appearance. In addition, the anchoring layer can also be given functions such as an antistatic effect by adding an antistatic agent. In addition, a curing agent having an isocyanate resin can be mixed in the anchoring layer. By mixing a curing agent having an isocyanate resin, the heat resistance, weather resistance, and water resistance of the obtained vapor-deposited film can be further improved.

[0140] The method for forming the anchor layer is not particularly limited. As an example, the anchor layer can be formed by applying a resin solution constituting the anchor layer dissolved in a suitable solvent (e.g., methyl ethyl ketone, toluene, ethyl acetate, etc.) onto the layer formed by the methacrylic resin composition (I) using a roll coater, followed by drying at about 80° C. to about 100° C. for 30 seconds to 1 minute.

[0141] The vapor-deposited film of the present invention may further have a coating film on the surface of the vapor-deposited film. The coating film refers to a film formed by applying a coating composition, drying it as needed, and curing it. Various functions can be imparted by the coating film. As such functions, for example, decoration, scratch resistance, antistatic, antifouling, friction reduction, antifogging, anti-glare, light reflection prevention, high light reflection, adhesion, impact resistance, anti-adhesion, gas barrier, transparent conductivity, etc. can be cited. There is no particular limitation on the method of applying the coating composition, for example, methods such as roller coating, gravure coating, blade coating, dip coating, curtain coating, spray coating, and scraper bar coating can be used.

[0142] The vapor deposited film of the present invention can be used, for example, in automobile interior and exterior decoration, personal computer interior and exterior decoration, mobile terminal interior and exterior decoration, wearable terminal interior and exterior decoration, solar cell interior and exterior decoration, solar cell backplane, liquid crystal light guide plate, diffuser, backplane, reflector, polarizer protective film, phase difference film and other liquid crystal display film, surface protection film and other information equipment fields, optical fiber, optical switch, optical connector and other optical communication fields, automobile headlight, taillight lens, inner lens, instrument cover, automobile sunroof, glass window and other vehicle fields, glasses, corneal contact lens, endoscope lens, road sign, bathroom equipment, floor material, road light-transmitting plate, double-layer glass lens, skylight, carport, lighting lens, lighting cover, building material glue and other construction / building material fields, microwave cooking container (tableware), housing of home appliance, toys, sunglasses, stationery, solar concentrating film, etc. In addition, it can also be used as an alternative to the molded product using the transfer foil.

[0143] Specific uses of the transparent conductive film having a conductive vapor-deposited film include: window electrodes of photoelectric conversion elements of solar cells, electromagnetic shielding films for electromagnetic shielding, transparent radio wave absorbers, electrodes of input devices such as transparent touch panels, substrates for transparent electrodes for liquid crystal displays, organic EL displays or touch panels, etc.

[0144] Specific uses of gas barrier films having gas barrier vapor-deposited films include: surface panel components of small electronic mobile displays such as mobile phones and e-books, gas barrier components of organic EL elements, protective components of liquid crystal display elements (such as polarizer protective films, etc.), sealing components of quantum dot fluorescent elements, components used in photovoltaic power generation / solar cells, etc., components used in thin-film transistors, touch panels, electronic paper, etc., packaging materials for food, medicines, etc., etc.

[0145] Example

[0146] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0147] The measurement of physical properties and the like was carried out by the following methods.

[0148] (Polymerization conversion rate)

[0149] A gas chromatograph GC-14A manufactured by Shimadzu Corporation was connected with INERTCAP1 (df = 0.4 μm, 0.25 mm I.D. × 60 m) manufactured by GL Sciences Inc. as a column, and analysis was performed under the following conditions, and calculations were performed based on the conditions.

[0150] Inlet temperature = 250°C

[0151] Detector temperature = 250°C

[0152] Temperature conditions: maintain at 60°C for 5 minutes → increase the temperature to 250°C at 10°C / min → maintain at 250°C for 10 minutes

[0153] (Composition of each unit of the precursor polymer)

[0154] pass 13 The carbon ratios of the phenyl group of the α-methylstyrene unit, the carbonyl group of the methyl methacrylate unit, the phenyl group of the styrene unit, and the carbonyl group of the maleic anhydride unit were determined by C-NMR, and the composition of each unit was calculated from the ratio.

[0155] (Weight average molecular weight)

[0156] The weight average molecular weight (Mw) of each resin obtained in the manufacturing example is determined by GPC (gel permeation chromatography). 4 mg of the resin to be measured is dissolved in 5 ml of tetrahydrofuran to prepare a sample solution. The temperature of the column oven is set to 40°C, and 20 μl of the sample solution is injected into the device under the condition of an eluent flow rate of 0.35 ml / min, and the chromatogram is measured. GPC measurement is performed on 10 points of standard polystyrene with a molecular weight in the range of 400 to 5000000, and a calibration curve showing the relationship between retention time and molecular weight is prepared. The Mw of the resin to be measured is determined based on the calibration curve. According to the chromatogram measured by GPC, the value equivalent to the molecular weight of the standard polystyrene is used as the molecular weight of the copolymer.

[0157] Equipment: GPC equipment HLC-8320 manufactured by Tosoh Corporation

[0158] Separation column: TSK guardcolum Super HZ-H, TSKgel HZM-M and TSK gel Super HZ4000 manufactured by Tosoh Corporation connected in series

[0159] Eluent: Tetrahydrofuran

[0160] Eluent flow rate: 0.35ml / min

[0161] Column temperature: 40°C

[0162] Detection method: Differential refractive index (RI)

[0163] (Composition of each unit in the methacrylic acid copolymer)

[0164] The composition of the α-methylstyrene unit and the styrene unit is the same as that of each unit of the precursor polymer.

[0165] use 1The methacrylic acid copolymer was analyzed by H-NMR (manufactured by Bruker; trade name ULTRA SHIELD 400 PLUS). 1 H-NMR measurement was used to determine the content (mol%) of each monomer unit in the methacrylic copolymer, such as the imide unit (glutarimide and maleimide), methyl methacrylate unit, and aromatic vinyl (α-methylstyrene and styrene) unit, and the content (mol%) was converted into the content (weight%) using the molecular weight of each monomer unit. In addition, infrared spectrophotometer was used to measure the content (mol%) at 1700 cm -1 The absorption intensity of the peaks attributable to the carbonyl unit of maleimide and 1780 cm -1 The imidization ratio (Rm) of maleic anhydride was calculated by the absorption intensity of the peak attributable to the carbonyl group of maleic anhydride near 13 The maleic anhydride amount (m) and the imidization ratio (Rm) of the precursor polymer determined by C-NMR were determined by the following formula and were defined as the maleic anhydride amount (M) in the methacrylic copolymer.

[0166] Maleic anhydride amount (M) = m × (100-Rm) / 100

[0167] Furthermore, using an infrared spectrophotometer, the -1 The absorption intensity of the peak attributed to the carbonyl group of glutarimide and the peak at 1700 cm -1 The ratio of the glutarimide unit to the maleimide unit in the methacrylic copolymer was determined by using the absorption intensity of the peak attributable to the carbonyl unit of maleimide in the vicinity. 1 The contents of the glutarimide units and the maleimide units in the methacrylic acid-based copolymer were determined from the amount of the imide units in the methacrylic acid-based copolymer determined by H-NMR and the ratio of the glutarimide units to the maleimide units.

[0168] (Total transmittance; Tt)

[0169] The methacrylic resin composition obtained in the production example was press-formed into a sheet having a thickness of 3 mm. The total light transmittance of the press plate was measured using a haze meter (manufactured by Murakami Color Laboratory; trade name: HM-150) in accordance with JIS K7361-1.

[0170] (Glass transition temperature; Tg)

[0171] The methacrylic resin composition obtained in the manufacturing example was dissolved in chloroform, reprecipitated with methanol, and then the precipitated resin was vacuum dried at 100°C for more than 12 hours. The vacuum-dried resin was heated to 250°C once, cooled to room temperature, and then heated from room temperature to 200°C at 10°C / min using a differential scanning calorimeter (DSC-50 (product number) manufactured by Shimadzu Corporation) in accordance with JIS K7121. The DSC curve was measured under such conditions. The midpoint glass transition temperature obtained from the DSC curve measured at the second heating was used as the glass transition temperature in the present invention.

[0172] (1% thermogravimetric reduction temperature)

[0173] The methacrylic resin composition obtained in the preparation example was heated at 10°C / min in a nitrogen atmosphere using a thermogravimetric measuring apparatus (TGA-50 manufactured by Shimadzu Corporation), and the temperature at which the weight was reduced by 1% from 200°C was defined as the 1% thermogravimetric reduction temperature.

[0174] (Saturated water absorption)

[0175] The methacrylic resin composition obtained in the manufacturing example is press-formed and then cut to obtain a square test piece with a thickness of 3 mm and a side of 50 mm. The test piece is vacuum dried for 24 hours at a temperature of 80°C and 5 mmHg. Then, the test piece is cooled in a dryer. Take out the test piece from the dryer and immediately measure the mass (initial mass). Next, immerse the test piece in distilled water at 23°C. Take out the test piece from the water, wipe off the water attached to the surface, and measure the mass. Repeat the immersion in distilled water and mass measurement until the mass change disappears. The saturated water absorption rate is calculated according to the following formula from the mass (water absorption mass) when the mass change disappears and the initial mass.

[0176] Saturated water absorption rate (%) = [(water absorption mass - initial mass) / initial mass] × 100

[0177] (Unnotched Charpy Impact Strength)

[0178] The methacrylic resin composition obtained in the manufacturing example was press-formed and then cut to obtain a test piece with a thickness of 4 mm, a length of 80 mm, and a width of 10 mm. Each test piece was measured under the conditions of 23° C. and a relative humidity of 50% by a method based on the method described in JIS K7111-1 / 1eU. The measurement was performed 10 times, and the average value of the Charpy impact value was adopted.

[0179] (Melt Flow Rate; MFR)

[0180] The methacrylic resin composition obtained in the production example was dissolved in chloroform and reprecipitated with methanol, and the precipitated resin was vacuum dried at 100° C. for 12 hours or more. The vacuum dried resin was measured at 230° C. and 3.8 kg load according to JIS K7210.

[0181] (Wetting tension)

[0182] The methacrylic resin composition obtained in the production example was press-molded into a sheet having a thickness of 3 mm. The wetting tension was measured in accordance with JIS K6768 at 23° C. and a relative humidity of 50% using a mixed solution for wetting tension test (manufactured by Wako Pure Chemical Industries, Ltd.).

[0183] (Heating shrinkage)

[0184] A 100 mm × 30 mm test piece was cut out from the substrate film of the example and the comparative example. A straight line of 70 mm in length was written on the surface of the test piece, and the test piece was heated in a forced circulation air constant temperature oven maintained at 110°C for 30 minutes. Then, the length of the written straight line (L (mm)) was read using a ruler, and the heat shrinkage was calculated using the following formula. The test piece with a heat shrinkage of less than 1.0% was set as qualified.

[0185] Heating shrinkage (%) = [(70-L) / 70] × 100

[0186] (Dimensional stability when hygroscopic)

[0187] The substrate film of the embodiment and the comparative example was placed in an environment of temperature 23°C and relative humidity 50% for more than 24 hours, cut into 100mm×20mm, and the initial size was measured. Then, the test piece was kept in an environment of temperature 85°C and relative humidity 85%RH for 96 hours. The size of the test piece taken out was measured again as the size after the test. The dimensional change rate was calculated by the following formula, and the test piece with a dimensional change rate of -30.0 to 0.0% was qualified.

[0188] Dimension change rate (%) = ((size after test - initial size) / initial size) × 100

[0189] (Stretchability)

[0190] <Uniaxial stretchability>

[0191] A 50 mm × 40 mm film sheet was cut out from the unstretched film of the examples and comparative examples. The film sheet was placed in a tensile testing machine (AG-IS 5kN manufactured by Shimadzu Corporation) with a chuck spacing of 20 mm, and uniaxially stretched at an area stretching ratio of 2 times in the longitudinal direction at a stretching temperature of glass transition temperature + 10°C and a stretching speed of 500% / min, and cooled to 100°C or less in 2 minutes. In this test, 10 film sheets were evaluated as follows.

[0192] A: Among 10 films, at least 5 films have no cracks or ruptures.

[0193] B: Among 10 films, 4 or less films have no cracks or ruptures.

[0194] <Biaxial stretchability>

[0195] Ten substrate films (biaxially stretched films) of Examples and Comparative Examples were subjected to the following evaluations.

[0196] A: Among 10 films, at least 5 films have no cracks or ruptures.

[0197] B: Among 10 films, 4 or less films have no cracks or ruptures.

[0198] Based on the evaluation results of uniaxial stretchability and biaxial stretchability, the quality of stretchability was judged according to the following criteria.

[0199] ◎: Both uniaxial stretchability and biaxial stretchability were judged as A

[0200] ○: Uniaxial stretchability or biaxial stretchability is judged as A

[0201] ×: Uniaxial stretchability and biaxial stretchability are judged as B

[0202] (Adhesion to vapor deposited film)

[0203] SRC-10-D (manufactured by Japan Vacuum Technology Co., Ltd.) was used with a 4.5×10 -5 The three metals of aluminum, tin and indium were vacuum-deposited onto the substrate films of the examples and comparative examples. The film thickness of the deposited aluminum, tin and indium was set to a range of 500 to 1500 angstroms. A cutter was used to cut the surface of the deposited film at 1 cm 2 100 grid-like cuts were made in the area, and the evaluation was performed by a Sellotape (registered trademark) peeling test.

[0204] ○: No peeling was observed in the vapor-deposited film or less than 10 pieces of peeling were observed

[0205] ×: 10 or more peelings were observed in the vapor deposited film

[0206] (Dimensional stability)

[0207] SRC-10-D (manufactured by Japan Vacuum Technology Co., Ltd.) was used with a 4.5×10 -5 Aluminum, tin and indium are vacuum-deposited onto the substrate films of the embodiments and comparative examples. The film thickness of the deposited aluminum, tin and indium is set in a range of 500 to 1500 angstroms. Heat at 145°C for 60 minutes with the deposited film on top, and then cool at room temperature (23°C) for 1 hour. Then, place the sample in a horizontal plane with the deposited film on top, and measure the height of the center from the horizontal plane (curl value A). In addition, measure the heights of the four corners from the horizontal plane, and calculate the average value (curl value B). The value (AB) obtained by subtracting the curl value B from the curl value is used as the curl value, which is used as a criterion for determining dimensional stability.

[0208] ○: Curl value is within the range of 0 to 50 mm

[0209] ×: The curl value is outside the range of 0 to 50 mm

[0210] <Examples of various materials>

[0211] The following materials are used for the methacrylic copolymer (a), the styrene-maleic anhydride copolymer and the methacrylic resin of the present invention.

[0212] Methacrylic acid copolymer (a-6): PLEXIMID TT50 manufactured by Polyplastics Evonik Corporation (Mw = 76,000, MMA / N-methylglutarimide = 30% / 70%, Tg = 151°C, saturated water absorption = 3.8%)

[0213] Methacrylic acid copolymer (a-7): PLEXIGLAS hw55Clear manufactured by Polyplastics Evonik Corporation (Mw = 141000, MMA / styrene / maleic anhydride = 74% / 15% / 9%, Tg = 121°C, saturated water absorption = 2.2%)

[0214] Styrene-maleic anhydride copolymer: XIRAN3500 manufactured by POLYSCOPE (Mw = 80,000, styrene / maleic anhydride = 74% / 26%, Tg = 160°C, saturated water absorption = 0.3%)

[0215] Methacrylic resin: Parapet HR manufactured by Kuraray Co., Ltd. (Mw = 90,000, MMA / MA = 99.3% / 0.7%, Tg = 117°C, saturated water absorption = 2.0%)

[0216] (Production Example: Precursor polymer)

[0217] The precursor polymers (p-1) to (p-5) of this production example were produced by the following method.

[0218] Precursor polymer (p-1) to (p-2)

[0219] Into an autoclave with a stirrer, 68.0 parts by mass of purified methyl methacrylate (MMA), 28.0 parts by mass of α-methylstyrene (αMSt), 7.0 parts by mass of styrene (St), 0.05 parts by mass of 2,2'-azobis(2-methylpropionitrile) (AIBN) and 0.01 parts by mass of n-octyl mercaptan (n-OM) were added and uniformly dissolved to obtain a polymerization raw material. Nitrogen was blown into the reaction raw material to remove dissolved oxygen to 3ppm. Next, the continuous flow tank reactor equipped with a brine condenser was replaced with nitrogen. The polymerization raw material was continuously supplied to the above-mentioned tank reactor at a constant flow rate with an average residence time of 3.0 hours, and bulk polymerization was carried out at a polymerization temperature of 140°C, and a liquid containing a precursor polymer was continuously discharged from the tank reactor. It should be noted that the pressure in the tank reactor was adjusted using a pressure regulating valve connected to the brine condenser. The polymerization conversion rate is the value recorded in Table 1. Next, the liquid discharged from the reactor is heated to 210°C and supplied to a twin-screw extruder controlled at 230°C. The volatile components mainly composed of unreacted monomers are separated and removed in the twin-screw extruder, and the precursor polymer is extruded in the form of strands. The strands are cut with a granulator to obtain a precursor polymer (p-1). The weight average molecular weight Mw of the obtained precursor polymer (p-1) is measured. The results are shown in Table 1. In addition, 77.5 parts by mass of purified methyl methacrylate (MMA), 17.5 parts by mass of α-methylstyrene (αMSt), 5.0 parts by mass of styrene (St), 0.04 parts by mass of 2,2'-azobis(2-methylpropionitrile) (AIBN) and 0.053 parts by mass of n-octyl mercaptan (n-OM) are used, and the average residence time is changed to 2.5 hours. In addition, the same operation as the preparation method of the above-mentioned precursor polymer (p-1) is performed to obtain a precursor polymer (p-2). Table 1 also shows the polymerization conversion rate and weight average molecular weight Mw of the precursor polymer (p-2).

[0220] Precursor polymer (p-3)

[0221] Into an autoclave with a stirrer, 60.0 parts by mass of purified methyl methacrylate (MMA), 25.0 parts by mass of α-methylstyrene (αMSt), 15.0 parts by mass of maleic anhydride (Mah), 0.005 parts by mass of 2,2'-azobis(2-methylpropionitrile) (AIBN) and 0.02 parts by mass of n-octyl mercaptan (n-OM) were added and uniformly dissolved to obtain a polymerization raw material. Nitrogen was blown into the reaction raw material to remove dissolved oxygen to 3ppm. Next, the continuous flow tank reactor equipped with a brine condenser was replaced with nitrogen. The polymerization raw material was continuously supplied to the above-mentioned tank reactor at a constant flow rate with an average residence time of 2 hours, and bulk polymerization was carried out at a polymerization temperature of 130°C, and a liquid containing a precursor polymer was continuously discharged from the tank reactor. It should be noted that the pressure in the tank reactor was adjusted using a pressure regulating valve connected to the brine condenser. The polymerization conversion rate is the value recorded in Table 1. Next, the liquid discharged from the reactor was heated to 230°C and supplied to a twin-screw extruder controlled at 240°C. The volatile components mainly composed of unreacted monomers were separated and removed in the twin-screw extruder, and the precursor polymer was extruded in the form of strands. The strands were cut with a pelletizer to obtain a precursor polymer (p-3). The weight average molecular weight Mw of the obtained precursor polymer (p-3) was measured. The results are shown in Table 1.

[0222] Precursor polymer (p-4)

[0223] 75.0 parts by mass of purified methyl methacrylate (MMA), 25.0 parts by mass of α-methylstyrene (αMSt), 0.004 parts by mass of 2,2'-azobis(2-methylpropionitrile) (AIBN) and 0.02 parts by mass of n-octyl mercaptan (n-OM) were added to an autoclave with a stirrer and uniformly dissolved to obtain a polymerization raw material. Nitrogen was blown into the reaction raw material to remove dissolved oxygen to 3 ppm. Next, the continuous flow tank reactor equipped with a brine condenser was replaced with nitrogen. The polymerization raw material was continuously supplied to the above-mentioned tank reactor at a constant flow rate with an average residence time of 3 hours, and bulk polymerization was carried out at a polymerization temperature of 130°C, and a liquid containing a precursor polymer was continuously discharged from the tank reactor. It should be noted that the pressure in the tank reactor was adjusted using a pressure regulating valve connected to the brine condenser. The polymerization conversion rate is the value recorded in Table 1. Next, the liquid discharged from the reactor was heated to 230°C and supplied to a twin-screw extruder controlled at 240°C. The volatile components mainly composed of unreacted monomers were separated and removed in the twin-screw extruder, and the precursor polymer was extruded in the form of strands. The strands were cut with a pelletizer to obtain a precursor polymer (p-4). The weight average molecular weight Mw of the obtained precursor polymer (p-4) was measured. The results are shown in Table 1.

[0224] Precursor polymer (p-5)

[0225] According to the method for producing the copolymer (A) described in the [Example] section of Japanese Patent Publication No. 2003-231785, an MS resin (a copolymer of methyl methacrylate (MMA) and styrene (St)) was polymerized. The mass ratio of MMA and St put into the autoclave was changed to obtain a precursor polymer (p-5) having a content of styrene monomer units of 20% by mass. The weight average molecular weight Mw of the obtained precursor polymer (p-5) was measured. The results are shown in Table 1.

[0226] <Production Example 1>

[0227] The precursor polymer (p-1) is supplied at 15 kg / hour to the conveying section of a twin-screw extruder (manufactured by Nippon Steel Works, Ltd.; trade name TEX30α-77AW-3V) which is composed of a conveying section, a melt-kneading section, a devolatilization section and a discharge section, and the screw speed is set to 150 rpm and the temperature is set to 210-270°C. In the melt-kneading section provided with a kneading block, the amount of monomethylamine added is adjusted in such a way that the content of the structural unit derived from glutarimide in Table 1 is obtained, and the precursor polymer (p-1) is reacted with the monomethylamine by injecting it from the additive supply port of the twin-screw extruder. It should be noted that the melt-kneading section is almost always composed of a kneading disk, and sealing elements are installed at both ends thereof. In the devolatilization section, by-products and excess monomethylamine are volatilized from the molten resin passing through the melt-kneading section and discharged through a plurality of vents.

[0228] The molten resin extruded in the form of strands from a die disposed at the end of the discharge portion of the twin-screw extruder was cooled in a water tank and then cut using a pelletizer to obtain a granular methacrylic copolymer (a-1). The content of the structural unit derived from glutarimide in the methacrylic copolymer (a-1) was 53% by weight. The composition and weight average molecular weight Mw of the methacrylic copolymer (a-1) are shown in Table 1.

[0229]

[0230] <Production Example 2>

[0231] A methacrylic acid copolymer (a-2) was obtained by the same method as in Example 1 except that the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 70 wt %. Table 1 shows the composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-2).

[0232] <Production Example 3>

[0233] A methacrylic acid copolymer (a-3) was obtained by the same method as in Example 1 except that the precursor polymer (p-2) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 38% by weight. The composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-3) are shown in Table 1.

[0234] <Production Example 4>

[0235] A methacrylic acid copolymer (a-4) was obtained by the same method as in Example 1 except that the precursor polymer (p-3) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 25% by weight and the content of the structural unit derived from maleimide was 15% by weight. The composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-4) are shown in Table 1.

[0236] <Production Example 5>

[0237] A methacrylic acid copolymer (a-5) was obtained by the same method as in Example 1 except that the precursor polymer (p-2) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 15% by weight. The composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-5) are shown in Table 1.

[0238] <Production Example 6>

[0239] A methacrylic acid copolymer (a-8) was obtained by the same method as in Example 1 except that the precursor polymer (p-4) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 30% by weight. The composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-8) are shown in Table 1.

[0240] <Production Example 7>

[0241] A methacrylic acid copolymer (a-9) was obtained by the same method as in Example 1 except that the precursor polymer (p-5) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 48% by weight. The composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-9) are shown in Table 1.

[0242] <Production Example 8>

[0243] The methacrylic copolymer (a-1) was melt-kneaded and extruded at 250° C. using a twin-screw extruder having a shaft diameter of 20 mm to obtain a methacrylic resin composition (I-1).

[0244]

[0245] <Production Examples 9 to 19>

[0246] Methacrylic resin compositions (I-2) to (I-12) were obtained by the same method as in Production Example 6 except for the formulations described in Table 2. Table 2 shows the evaluation results.

[0247] <Example 1>

[0248] The methacrylic resin composition (I-1) was dried at 80°C for 12 hours. A 20mmφ single screw extruder (manufactured by OCS) was used to extrude the methacrylic copolymer (a-1) from a 150mm wide T-die at a resin temperature of 260°C, and the methacrylic copolymer (a-1) was pulled with a roller having a surface temperature of 110°C to obtain an unstretched film having a width of 110mm and a thickness of 160μm. The unstretched film obtained was cut into 100mm×100mm, and was subjected to sequential biaxial stretching (4 times in terms of area ratio) at a stretching temperature of glass transition temperature+10°C with a stretching speed of 500% / min in one direction and a stretching ratio of 2 times in one direction using a pantograph biaxial stretching tester (manufactured by Toyo Seiki Co., Ltd.), and cooled to less than 100°C in 2 minutes and taken out to obtain a biaxially stretched film (substrate film) having a thickness of 40μm. The evaluation results of the obtained substrate film are shown in Table 3.

[0249] <Examples 2 to 5, Comparative Examples 1 to 7>

[0250] The evaluation results of the obtained base films are shown in Table 3, except that the methacrylic resin compositions (I-2) to (I-12) were used instead of the methacrylic resin composition (I-1).

[0251]

[0252] As shown in Table 3, the substrate films obtained in Examples 1 to 5 have excellent stretchability by using methacrylic resin compositions (I-1) to (I-5) having high Charpy impact strength and excellent fluidity. In addition, the resin composition is heat-resistant and has low water absorption, so the substrate films of Examples 1 to 5 have low thermal shrinkage and excellent dimensional stability. In addition, due to the high wetting tension, the substrate films of Examples 1 to 5 have excellent adhesion to the vapor-deposited film. From the above, it can be seen that the substrate films of Examples 1 to 5 are suitable as substrates for vapor deposition. In contrast, for the substrate films (Comparative Examples 1 to 4) using methacrylic resin compositions (I-6) to (I-9) and (I-12) that have insufficient heat resistance and low water absorption, the heat shrinkage is high and the dimensional stability is also deteriorated. In addition, the base film using the methacrylic resin composition (I-6) with low wetting tension (Comparative Example 1) and the base film using the resin composition (I-10) with low Charpy impact strength (Comparative Example 5) had reduced stretchability and adhesion to the vapor-deposited film. The base film using the methacrylic resin composition (I-11) with low thermal decomposition resistance (Comparative Example 6) had reduced stretchability.

Claims

1. A substrate film for vapor deposition, which is formed from a methacrylic resin composition (I) containing a methacrylic copolymer (a) and having a glass transition temperature of 135° C. or higher, and has a film thickness of 10 to 80 μm and a biaxial stretching ratio of 1.5 to 8 times, The methacrylic copolymer (a) comprises 5 to 73% by mass of methyl methacrylate units, 25 to 70% by mass of a structural unit (r) represented by the following formula (1), 1 to 48% by mass of an α-methylstyrene unit, 1 to 48% by mass of at least one selected from the group consisting of a styrene unit and a maleic anhydride unit, and 0 to 20% by mass of an unsubstituted or N-substituted maleimide unit. In formula (I), R 1 are each independently a hydrogen atom or a methyl group, R 2 It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms including an aromatic ring. 2 . The vapor deposition substrate film according to claim 1 , which is formed from a methacrylic resin composition having a glass transition temperature of 145° C. or higher. 3 . The vapor deposition substrate film according to claim 1 , which is formed from a methacrylic resin composition having a saturated water absorption of 3.0% by mass or less. 4 . A vapor-deposited film comprising the base film according to claim 1 and a vapor-deposited film provided on at least one surface of the base film.

5. The evaporated film according to claim 4, wherein: The vapor-deposited film is a conductive vapor-deposited film.

6. The evaporated film according to claim 4, wherein: The vapor-deposited film is a gas barrier vapor-deposited film.

7. A method for producing a substrate film according to claim 1, comprising the steps of forming a methacrylic resin composition (I) containing a methacrylic copolymer (a) and having a glass transition temperature of 135° C. or higher to obtain a film and biaxially stretching the film to 1.5 to 8 times in terms of area ratio, The methacrylic copolymer (a) comprises 5 to 73% by mass of methyl methacrylate units, 25 to 70% by mass of a structural unit (r) represented by the following formula (1), 1 to 48% by mass of an α-methylstyrene unit, 1 to 48% by mass of at least one selected from the group consisting of a styrene unit and a maleic anhydride unit, and 0 to 20% by mass of an unsubstituted or N-substituted maleimide unit. In formula (I), R 1 are each independently a hydrogen atom or a methyl group, R 2 It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms including an aromatic ring.

Citation Information

Patent Citations

  • Continuous modification of resin

    JP1986026924B2

  • Transparent conductive laminate

    JP1990006126A

  • Drawn film or sheet

    JP1994256537A

  • Method for producing imidized copolymers

    JP1995042332B2

  • Method for imidating styrene / maleic anhydride polymer

    JP1997100322A